Malaysia diseases visualizer using proportional symbol map / Qamaryna Kamarudin - Kamarudin, Qamaryna (2019)
Data visualization is the representation of data as a means to educate and inform a targeted group of people of accurate data retrieved from a reliable source. There comes a need for data visualization when there is large amount of data that requires to be visually presented in a way that assists the users to effortlessly comprehend the data. Currently, the health care data in Malaysia is stored in Malaysia Health Data Warehouse (MyHDW) in the form of lengthy and tedious reports, which is time consuming and not appealing to the public. Hence, there is a need to properly visualize the data in order to make the representation of health care data more attractive to the users. This project will develop a data visualization webpage of three diseases in Malaysia from the year 2014 to 2016 using D3.js. The visualization will allow easy tracking of diseases in Malaysia as well as identification of the hotspots of the diseases. This visualization can benefit the people of Malaysia as it can act as a basis for the decision-making of the government to take the necessary actions on widespread diseases and focus on areas that need more attention.